2018
DOI: 10.1001/jamapsychiatry.2018.1214
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Heroin Dependence in Newly Incident Heroin Users

Abstract: Some 30 to 50 US residents die of heroin overdoses each day. 1 By comparison, an estimated 300 to 520 individuals start heroin use each day. 2 For first-time users, these odds of overdose death might seem remote. For this reason, clinicians and public health practitioners deserve more compelling evidence to share with people who contemplate trying heroin. Seeking reproducible results via 15 US epidemiological samples, we estimate how often newly incident heroin users become dependent on heroin. Estimation focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…As discussed elsewhere (Cadet, 2019), because repeated drug use in humans is not enough to reach a SUD DSM-V diagnosis, we have added contingent footshocks during drug SA to encompass one additional DMS criterion, namely, compulsive drug taking in the presence of adverse consequences. This approach is consistent with the observations that, in clinical situations, only small percentages of individuals continue to misuse drugs when faced with legal and financial consequences (Anthony et al, 1994;Miller and Flaherty, 2000;Santiago Rivera et al, 2018). It needs to be also noted that there exists a substantial number of individuals who use opioids without meeting criteria for OUD (Korf et al, 2010;Zaaijer et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…As discussed elsewhere (Cadet, 2019), because repeated drug use in humans is not enough to reach a SUD DSM-V diagnosis, we have added contingent footshocks during drug SA to encompass one additional DMS criterion, namely, compulsive drug taking in the presence of adverse consequences. This approach is consistent with the observations that, in clinical situations, only small percentages of individuals continue to misuse drugs when faced with legal and financial consequences (Anthony et al, 1994;Miller and Flaherty, 2000;Santiago Rivera et al, 2018). It needs to be also noted that there exists a substantial number of individuals who use opioids without meeting criteria for OUD (Korf et al, 2010;Zaaijer et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…The primary neurocircuitry elements involved (basal ganglia, extended amygdala, and prefrontal cortex) and their molecular connections to the cycle of addiction (intoxication, withdrawal, and preoccupation) are broadly understood. However, there is clear variability in the functioning of this neurocircuitry among individuals as evidenced by only 20–30% of people who use heroin becoming addicted 9 , 10 and only 8–12% of chronic pain patients prescribed opioids developing OA 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Opioid use continues to pose significant risk to individuals throughout the globe, especially in the United States. Data from population-based epidemiological surveys from 2002-2016 in the United States revealed that approximately 30% of individuals who started heroin use met DSM-IV criteria for opioid dependence within one year of initiation (1). In addition, the most recent estimates from the Global Burden of Diseases, Injuries, and Risk Factors Study revealed that the global prevalence of opioid dependence was 510 people per population of 100,000, and the United States had the highest prevalence rate among all countries (1,347 persons per 100,000 population) (2).…”
Section: Introductionmentioning
confidence: 99%